Pemanfaatan Sampah Plastik Jenis Pet (Polyethylene Terephthalate) Sebagai Bahan Tambahan Pembuatan Paving Block Model Hexagon - Mahagadha, I Made Bayu; Barus, Linda; Trigunarso, Sri Indra (MIDWIFERY JOURNAL, 2023)
Background: This research will utilize shredded plastic waste type PET (Polyethylene Terephthalate) as an added material to reduce sand aggregate in the manufacture of paving blocks.Purpose: The aim is to determine the compressive strength and positive effect of adding PET type plastic waste to the solution for handling plastic waste.Methods: This research is a type of experimental research, experimental research or experimental research is a research by conducting experimental activities, which aims to determine the symptoms or effects that arise, as a cause and effect of the existence of certain treatments or experiments (Notoadmodjo, 2014 ). In this research design, the ratio of cement sand to sand 1:6: 0.45%, 0.5%, 0.55% plastic pieces with variations in the size of the PET plastic pieces are 1 cm and 1.5 cm. The composition of PET plastic in each Paving Block treatment was 0.45%, 0.5%, 0.55% and used variations of 1 cm and 1.5 cm of PET plastic pieces with 4 replications.Results: From the results of research that has been carried out the maximum paving block strength in this study is at sample number A1 with a composition of 0.45% addition of PET plastic and a variation of 1 cm PET plastic pieces which is 198.89 kg/cm2 and the lowest pressure strength value is found. the sample number A3 with a value of 137.12 kg/cm2 occurs in the use of 0.55% PET plastic waste composition and with a cut variation of 1 cm.Conclusion: With the results above, paving blocks have the highest pressure strength, namely 198.89 kg/cm2 with a composition of 0.45% of crushed PET type plastic waste and a variation of 1 cm in size. In accordance with SNI03-0691-1996 regarding quality standards of paving blocks. Keyword : Paving Block, Compressive Strength, PET Plastic Waste ABSTRAK Latar Belakang: Penelitian ini akan memanfaatkan cacahan sampah plastik jenis PET (Polyethylene Terephthalate) sebagai bahan tambah untuk mengurangi agregat pasir pada pembuatan paving block.Tujuan: Untuk mengetahui kuat tekan dan pengaruh positif dalam penambahan limbah plastik jenis PET terhadap solusi penanganan limbah plastik.Metode:Penelitian ini merupakan jenis penelitian eksperimen, penelitian eksperimen atau percobaan (experimental research) adalah suatu penelitian dengan melakukan kegiatan percobaan (experiment), yang bertujuan untuk mengetahui gejala atau pengaruh yang timbul, sebagai sebab akibat dari adanya perlakuan tertentu atau eksperimen tersebut (Notoadmodjo, 2014). Pada rancangan penelitian ini akan menggunakan jumlah perbandingan semen pasir 1 : 6 : cacahan plastik 0,45 %, 0,5 %, 0,55 % dengan variasi ukuran potongan plastik PET yaitu 1 cm dan 1,5 cm. Adapun komposisi Plastik PET pada setiap perlakuan Paving Blok adalah 0,45%, 0,5%, 0,55% dan menggunakan variasi potongan plastik PET sebesar 1 cm dan 1,5 cm dengan 4 kali replikasi.Hasil: Dari hasil penelitian yang telah dilakukan kekuatan paving block maksimal pada penelitian ini adalah berada pada nomor sampel A1 dengan komposisi penambahan plastik PET sebanyak 0,45% dan variasi potongan plastik PET 1 cm yaitu sebesar 198,89 kg/cm2 dan nilai kuat tekanan terendah terdapat pada nomor sampel A3 dengan nilai sebesar 137,12 kg/cm2 terjadi pada penggunaan komposisi cacahan sampah plastik PET 0,55% dan dengan variasi potongan 1 cm.Kesimpulan: Dengan hasil di atas paving block yang memiliki kuat tekanan tertinggi yaitu 198,89 kg/cm2 dengan komposisi 0,45% cacahan sampah plastik jenis PET dan variasi ukuran potongan 1 cm. Sesuai dengan SNI03-0691-1996 tentang baku mutu paving block. Kata Kunci: Paving Block, Kuat Tekan, Sampah Plastik PET